A Bibliography of Jewish Education in the United States - Drachler, Norman (Wayne State University Press, 2017)
This book contains entries from thousands of publications whether in English, Hebrew, Yiddish, and German-books, research reports, educational and general periodicals, synagogue histories, conference proceedings, bibliographies, and encyclopedias-on all aspects of Jewish education from pre-school through secondary education